Inversion tectonics, interference pattern and extensional fault-related folding in the Eastern Anti-Atlas, Morocco - Robert-Charrue, Charles; Burkhard, Martin (My University, 2008)
The Anti-Atlas belt of Morocco is a Variscan chain which appears as a huge anticlinorium oriented NE-SW. In the internal part of this structure, the actual relief shows the basement cropping out as inliers (Piqué 2001) or boutonnières. The cover, a thick pile of Paleozoic sediments up to 12 km thick, is gently folded and of low grade metamorphism in its lower level. The lack of major décollement, of a deformation front or thrust-fault makes the Anti-Atlas an unusual type of belt, which does not fit with classic schemes. The Anti-Atlas has been considered to be a thick skinned fold belt, with the crystalline basement involved in the horizontal shortening and where the folding of the cover fits to a “buckle fold” mode (Burkhard et al. 2006). This structural style is determined by two key parameters: the total thickness of Paleozoic cover series and the relative abundance of shale vs. competent marker beds.
The Eastern Anti-Atlas has particular features which are not found elsewhere in the Anti-Atlas. Its location at the intersection between the NW-SE Ougarta chain and the ENE-WSW main body of the Anti-Atlas, produces an egg-box interference pattern. The significance of minor folds and thrusts in the competent beds and their particular orientation is examined. The fact that the cover in the Eastern Anti-Atlas is only 6 km thick, which changes the shale vs competent beds ratio, influences its structural style. The feature that distinguishes the most Eastern Anti-Atlas is the presence of large E-W normal faults affecting the whole structure and creating extensional fault-related folding in the cover.
Keywords: Anti-Atlas; inversion tectonics; thick vs thin skinned tectonics; variscan; extensional fault-related folding